PENERAPAN MACHINE LEARNING REKAM MEDIS POLI ANAK DENGAN MODEL K-MEANS DALAM MELIHAT PENDATA PASIEN - Mutammimul Ula (Universitas Trilogi, 2023)
The application of machine learning in information technology has a big impact and change, especially in the health sector. Pukesmas Muara Satu North Aceh District is an implementing unit or assistant in Health under the Ministry of Health. Pukesmas Muara Satu has several polys where each poly has its own patient data, the children's polyclinic is currently one of the polyclinics with the most absences so it requires efficient medical record data collection, currently patient data recording still uses a manual system and the application of machine learning systems can complete the distribution of patient patterns in areas in the city of Lhokseumawe. The results of this study can manage patient data for the Children's Polyclinic at the Muara Satu Health Center and can make it easier for staff to record medical records for the Children's Polyclinic at the Health Center. The results of the pattern distribution can be seen in the name of the village of Blang Panyang. The number of patients is 92, C1 is 40.46488 and C2 is 2.151047, the Padang Sakti area is the number of patients is 109, male patients are 64 for a C1 value of 2.50038 and C2 is 2.151047. The final result of the k-means calculation value is Meuria Paloh, 37.9645, Blang Pulo 37.9645, East Batuphat 37.9645.